Phisic-mechaniks institute the name of G.V. Karpenko NAN of Ukraine : historical essay - G. L. Zvonkova (History of science and technology, 2015)
Displaying directions of scientific research conducted by scientists of the institute during the four decades of the second half of the twentieth century.